Complete cross strain protection against congenital cytomegalovirus infection requires a vaccine encoding key antibody (gB) and T-cell (immediate early 1 protein) viral antigens - Choi, K. Yeon; Qin, Yushu; El-Hamdi, Nadia; McGregor, Alistair (Frontiers in Immunology, 2025)
BackgroundCytomegalovirus is a leading cause of congenital disease, and multiple strains enable congenital CMV (cCMV) from both primary and non-primary infections. Therefore, a cross-strain protective cCMV vaccine is a high priority. Guinea pigs are the only small animal model for cCMV and guinea pig cytomegalovirus (GPCMV) encodes functional homolog proteins, including cell entry gB glycoprotein and non-structural immediate early 1 protein (IE1), which are essential for lytic infection. A gB vaccine antibody response fails to provide horizontal protection against highly cell-associated clinical GPCMV strain TAMYC compared to prototype strain 22122. Previously, a recombinant defective adenovirus (Ad) vaccine encoding IE1, a T cell antigen, provided high-level cCMV protection. In this study, we hypothesized that a combined Ad-based strategy encoding trimeric gB complex and IE1 (AdgB + AdIE1) could improve cross-strain protection against cCMV compared to a gB vaccine (AdgB).MethodsA preconception vaccine study was conducted to evaluate the immune response and ability of vaccines to provide cross-strain protection against cCMV. Seronegative female animals were assigned to three vaccine groups: Group 1 (AdgB), Group 2 (AdgB + AdIE1), and Group 3 (no vaccine). Animals were vaccinated following a previously defined protocol, and antibody ELISAs were used to evaluate the gB immune response (AD1, prefusion gB, and wild-type gB). Additionally, an IFNγ-ELISPOT assay was used to evaluate the IE1 T-cell response. During the second trimester, dams were challenged with GPCMV (22122 and TAMYC co-infection), and pregnancy proceeded to term. Viral loads in pup target organs (liver, lung, spleen, brain), blood, and placenta were evaluated.ResultsVaccinated dams elicited a higher gB neutralizing antibody response than that of experimentally infected convalescent animals. Antibodies recognized homolog AD1 gB domain as well as prefusion gB with a response surpassing that in GPCMV-infected convalescent animals. Group 2 dams also elicited a T cell response to IE1. Evaluation of viral load in pups demonstrated that the AdgB + AdIE1 vaccine reduced GPCMV transmission to below detectable limits compared to 91.7% in the unvaccinated group. In contrast, AdgB reduced cCMV transmission to 12% in the pups.ConclusionComplete cross-strain cCMV protection is a significant milestone in this model and is achieved by the inclusion of an antibody response to trimeric gB and T-cell response to IE1. Importantly, gB and IE1 responses can synergize and increase protection against cCMV, unlike prior approaches with gB and pp65 tegument proteins.